The impact of DaD on the school environment: the role of self-evaluation - Mastrolia, Alfonsina (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
Starting from the experience of Distance Learning (DaD) and/or Integrated Digital Didactics (DDI), the aim of the work was to understand what indicators might be useful for self-evaluation in this current transition to e-learning, to describe the changes produced on the learning environment and teaching methods, as a result of the integration of Information Communication Technologies (ICT). In order to achieve this objective, the contribution intends to advance a reflection on the construction of new indicators that would enable the evaluation of the social impact of DaD/DDI on the organisational dimension of schools, educational practices, and learning processes.